1991
DOI: 10.1111/j.1526-4610.1991.hed3108509.x
|View full text |Cite
|
Sign up to set email alerts
|

Arteriovenous Malformations and Migraine: Case Reports and an Analysis of the Relationship

Abstract: Some patients with cerebral arteriovenous malformations (AVMs) suffer recurrent migrainous attacks which meet the official criteria for migraine. The relationship of these attacks to the malformations has been poorly substantiated. Instances where attacks disappeared following surgical extirpation of an AVM support a relationship, but several other reported surgical outcomes do not. Both patients presented here had surgical results seemingly antithetical to a relationship: the attacks persisted in the first pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 6 publications
0
30
0
Order By: Relevance
“…Several authors have described the association between migraine and the presence of a CAVM [29,30]. In a study by STEELE et al [31], it is suggested that CAVM might play a role in the pathogenesis of migraine in HHT patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have described the association between migraine and the presence of a CAVM [29,30]. In a study by STEELE et al [31], it is suggested that CAVM might play a role in the pathogenesis of migraine in HHT patients.…”
Section: Discussionmentioning
confidence: 99%
“…Migraine with aura is classically related to cerebral arteriovenous malformations (AVMs). In most of these cases, MA ceasing after the removal of AVM has been documented, consistent with the definition of symptomatic migraine, but there are also sparse reports of cases unchanged after surgery (Has, 1991). The possibility of a causal relation is indirectly supported by the side of aura, being contralateral to the AVMs and the side of headache, being ipsilateral to the AVMs, as well as by the coexistence of MA and arteriovenous shunts in leptomeningeal angiomatosis (Sturge-Weber syndrome) .…”
Section: Symptomatic Migrainementioning
confidence: 78%
“…22) Frequent migraine-like headaches prevent a normal life, so resolution by removal of the occipital AVM is desirable. 3,8,17,20) Frequent migraines or migraine-like headaches should be a factor when considering surgical treatment for occipital AVM, even if the AVM is non-ruptured and/or giant. Middle age is not an indication for more conservative treatment.…”
Section: Discussionmentioning
confidence: 99%